Black adrenal adenoma: distinction from PPNAD. (3rd July 2012) - Kamalanathan, Sadishkumar; D M, Mahesh; K, Muruganandham; Basu, Debdatta
Abstract : A 22-year-old woman with features suggestive of Cushing's syndrome was found to have right adrenal mass on imaging studies. She had paradoxical rise in basal cortisol on dexamethasone suppression testing. Black adenoma of the right adrenal cortex, a pigmented adenoma consisting of compact cells with numerous pigments suggestive of melanin and lipofuscin was laproscopically removed from this patient. This case illustrates that in the setting of unilateral adrenal mass with paradoxical cortisol response with dexamethasone suppression testing, pigmented adrenal adenomas should be also suspected in addition to primary pigmented nodular adrenocortical disease.The decision to go with either unilateral or bilateral adrenalectomy should be based on the attributes of contralateral adrenal gland.